A transformation journey to creative and alternative planetary futures - Motti, Victor V. (Cambridge Scholars Publishing, 2019)
This book presents a counter-trend against nationalism, religious extremism, xenophobia, and racism. It advocates an alternative globalization based not on trade, the economy, and politics, but on humanity's transcendence to a collective consciousness. Inspired by a pantheist worldview, it applies an integral perspective toward strategic foresight and anticipation on the planetary scale. Controversial, disappearing, and emerging binary oppositions are explained within the framework of the mythology of the Lord of Wisdom versus the Ignorant Mind. It shows that our anticipatory planetary era mig.